Limitations to performance during alpine skiing - Ferguson, R. A. (Experimental Physiology, 2010)
Alpine skiing is characterized by high-intensity exercise of between 90 and 120 s duration that requires repeated phases of high-force isometric and eccentric contractions. The nature of these contractions, during which all fibre types are active, results in restricted blood flow to the working muscle, thereby reducing oxygen delivery and increasing metabolite accumulation. The consequence of this will be skeletal muscle fatigue, through both central and peripheral mechanisms, and a potential loss of motor control which will ultimately limit skiing performance.